Olahan Biren-san Sebagai Bahan Pembuat Durian Cookies Untuk Memenuhi Kebutuhan Kalori Tubuh - Maiditian , Nur Nahdia; Febrianti, Ajeng Dwi; Faradina, Shobiha (Najah: Journal of Research and Community Service, 2024)
Durian (Durio zibethinus) is a popular tropical fruit in Indonesia, including in Probolinggo Regency. In addition to its delicious meat, durian seeds can also be utilized as food. Durian seeds contain carbohydrates, proteins, minerals, and fiber that are good for health. However, the utilization of durian seeds is still limited to be thrown into waste. This study aims to examine the processing of durian seeds into food products that can be of economic value. The methods used include cleaning, boiling, peeling, slicing, drying, pulverizing and processing. The results showed that durian seeds can be processed into food products that have good texture, aroma and taste. Processing durian seeds into flour is used as an ingredient for making food products. While processing into Durian Cookies can be a healthy alternative snack. In conclusion, durian seeds have great potential to be developed into food products with high economic value and nutrition. Durian seed processing needs to be continuously studied and developed in order to increase its utilization in Indonesia.